Lev Semionovitch Vigotski e a Educação Escolar: uma prática educativa humanizadora como princípio para o desenvolvimento da consciência humana - Nascimento, Naiara Aparecida (2020)
This research aims to investigate to what extent the studies of Lev Semionovitch Vigotski (1896-1934) contribute to a school education based on the principles of a humanizing practice, non-exclusive, that sees the subject as a cultural being in its uniqueness. It starts from the assumption that a systematized practice, thought and articulated with reality, through a dialectical relationship between teaching and development, allows the humanization and formation of the subject, of his psychic possibilities, as well as of his conscience. In view of this, a theoretical-bibliographic research of an exploratory nature and a qualitative approach was developed based on the assumptions of historicalcultural psychology and historical-dialectical materialism, with an emphasis on the ideas and thinking of Vigotski, Marx and contemporary authors who share the same theoretical perspective. When considering that the psychology created by Vigotski is based on Marxist philosophy, it was decided to highlight aspects related to the life and work of Karl Marx (1818-1883), as the main representative of this theory and some developments related to the construction of his method, in order to identify the reasons that led Vigotski to base historicalcultural psychology on historical-dialectical materialism. Likewise, historical aspects inherent to Vigotski's life and work were brought to the fore, with the intention of unveiling the reasons that led the author to build a Marxist psychology with a view to the formation of a new man, for a just and egalitarian society, in plan with the Socialist Revolution of 1917. The theoretical deepening in aspects that concern the author's work and the context in which he was inserted allows to highlight as a result that Vigotski's studies contribute to school education, whereas, motivated by the need to understand the constitution of the subject inserted in a given culture, it defends that man is human and develops his conscience through cultural appropriation, in the relationship with the other, mediated by signs and instruments constructed collectively. His studies highlight that psychic development is not only conditioned to the organic basis, as was professed by other theories, but it develops mainly from the relationships he establishes with the world. In the context of education, this becomes extremely relevant as the scientific content, historically constructed and gathered by humanity, must be socialized and understood by the subject and educational practices need to be addressed in order to contemplate the students' particularities, while also respecting , its historical, social and cultural condition.